An introduction to African languages - Childs, George Tucker (John Benjamins Pub. Co., 2003)
This book introduces beginning students and non-specialists to the diversity and richness of African languages. In addition to providing a solid background to the study of African languages, the book presents linguistic phenomena not found in European languages. A goal of this book is to stimulate interest in African languages and address the question: What makes African languages so fascinating? The orientation adopted throughout the book is a descriptive one, which seeks to characterize African languages in a relatively succinct and neutral manner, and to make the facts accessible to a wide.